талабалар математик иқтидорининг ривожланишини таъминловчи педагогик технологиялар - Тлеубаева, Г.С. (SCIENCE and SOCIETY, 2020)
The article is devoted to the selection of gifted students and the organization of their teaching, which is one of the main problems of the "National Program of training staff", the author analyzes scientific researches, advanced pedagogical experience in the study of mathematical talent in students. At the same time, despite the fact that research related to advanced pedagogical and modern information and communication technologies is being carried out on a large scale, little attention is paid to the problem of determining the talent of students.